Optimisation of vehicle routing problem with time windows using Harris Hawks optimiser - S.W. Chai; M.R. Kamaluddin; M.F.F. Ab. Rashid (Journal of Mechanical Engineering and Sciences, 2022)
Vehicle routing problem is one of the combinatorial optimisation problems that have gained attraction for studies because of its complexity and significant impact to service providers and passengers. Vehicle routing problem with time windows (VRPTW) is a variant where vehicles need to visit the predetermined stop points within the given time frame. This problem has been widely studied and optimised using different methods. Since the performance of algorithms in different problems is dissimilar, the study to optimise the VRPTW is ongoing. This paper presents a VRPTW study for a public transportation network in Kuantan and Pekan districts, located in East Pahang, Malaysia. There were 52 stop points to be visited within two hours. The main objective of the study is to minimise the number of vehicles to be assigned for the routing problem subjected to the given time windows. The problem was optimised using a new algorithm known as Harris Hawks Optimiser (HHO). To the best of authors’ knowledge, this is the first attempt to build HHO algorithm for VRPTW problem. Computational experiment indicated that the HHO came up with the best average fitness compared with other comparison algorithms in this study including Artificial Bee Colony (ABC), Particle Swarm Optimisation (PSO), Moth Flame Optimiser (MFO), and Whale Optimisation Algorithm (WOA). The optimisation results also indicated that all the stop points can be visited within the given time frames by using three vehicles.